NEEDS OF COMPETENCIES IN FINANCIAL LITERACY FOR YOUTH WITH INTELLECTUAL DISABILITIES - Debora Pratiwi Sibarani; Mohammad Ali (Universitas Pendidikan Indonesia, 2022)
This study aims to analyze the need for financial literacy competencies in cognitive, psychomotor, and affective aspects for youth with intellectual disabilities at Yayasan Rumah Kampus Pena. The research method used is a mixed method with a case study approach and sequential explanatory design in two stages: a questionnaire instrument with 20 respondents as the subjects for quantitative data and field observation and in-depth interviews with parents, students, and experts for qualitative data. The reliability test of the questionnaire was carried out using the Kuder Richardson formula 20 (KR-20), with supporting analysis from the discriminating power test. In addition, experts analyzed the validity test of the questionnaire items using content validity. Meanwhile, the practitioners approved the observation guidance and interview questions where the research occurred as the results, 1). Financial literacy competencies of most students with intellectual disabilities were below the basic or minimum level of proficiency in financial literacy; 2). Competency Standards for Graduates should include knowledge, skills, and attitudes aspects with content areas of Money and Financial Transactions (Financial Planning and Management; 3). The experts' judgment on financial literacy competencies formulation received a score of 89% in the